Improvement of Insulin Sensitivity Increases Pregnancy Rate in Infertile PCOS Women: A Systemic Review - Liu, Yuqi; Li, Juan; Yan, Zhe; Liu, Dan; Ma, Jinfang; Tong, Nanwei (Frontiers in Endocrinology, 2021)
Background: Polycystic ovary syndrome (PCOS) is the most common cause of infertility in reproductive-age women. Insulin increases steroidogenesis, deranges granulosa cell differentiation, and affects follicle growth. However, results from randomized control trials (RCTs) were heterogeneous, and little strong evidence associated actual achievement of insulin sensitivity (IS) improvement with reproductive outcomes. Objectives: To identify evidence of the reproductive benefit of IS improvement in infertile PCOS women by analyzing eligible RCTs. Search Strategy: Different search strategies with unlimited keywords, including treatment, therapy, intervention, polycystic ovary syndrome/PCOS, insulin resistance, pregnancy, conceive, live birth, and randomized controlled trials/RCT were used in databases including Pubmed, Embase, and Web of Science to November 20th, 2021. Data Collection and Analysis: Two authors independently abstracted study details and assessed study quality. Main Results: Ten RCTs that covered different races and met the inclusion criteria were included for analysis and discussion. Clinical pregnancy rate was increased in infertile PCOS women when they had significant improvement of IS after treatment regardless of the various interventions (non-surgical). The benefits of IS improvement appeared superior in PCOS women without severe obesity. The effect of IS improvement on pregnancy rate was independent of the change of BMI. Conclusions: Nonsurgical therapeutic strategies that promote superior IS improvement may aid infertile PCOS women to increase their possibility of successful pregnancy regardless of the various interventions. The improvement of IS might be more important than the reduction of BMI in the improvement of pregnancy rate in infertile PCOS women.